Changes in the Technology of Moving Containers Inside Sea Container Terminals: From Conventional to Automated Technology - Robert MAREK (Communications of International Proceedings, 2021)
The need to cope with competition and the desire to build a competitive advantage on the market contribute to the implementation of automated handling, transport and handling equipment by container terminal operators. The motives of terminal operators in automating internal processes are varied and depend on the individual situation of a given container terminal on the market. They can evolve over time - gradually moving from a traditional terminal, partially automating it, reaching the level of full automation, or be subject to a revolution over time - i.e. building a fully automated sea container terminal, so called greenfield investment. The decision to automate a maritime container terminal may be dictated by the desire to increase the productivity of operations carried out inside the terminal and thus to take advantage of the opportunities that appear on the market. The study discusses various techniques and technologies of reloading, transport and handling operations carried out in sea container terminals and defines the concept of a traditional, semi-automated and fully automated terminal.
Keywords: Traditional Container Terminal; Semi-Automated Container Terminal; Automated Container Terminal; Techniques and Technologies Used in Marine Container Terminals.